Comparison of three serological tests to detect Paragonimus mexicanus infections in infected cats - Cornejo, William R. (2012)
Background: Paragonimiasis is a lung disease caused by Paragonimus trematodes genus. Human infection laboratory diagnosis is usually done by detection of parasite eggs in sputum or feces; however, findings may be negative and alternative diagnostic methods are required. Objectives: To compare three serologic tests for detection of Paragonimus mexicanus somatic antigen (PmAS) antibodies in serum samples of cats infected experimentally. Design: Experimental study. Setting: Instituto de Medicina Tropical “Daniel A. Carrión” bioterium, Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Biologic material: Domestic cats 4-6 years old and P. mexicanus (PmAS) crude somatic antigen. Interventions: Blood samples were collected from twelve domestic cats infected with P. mexicanus. Serum samples were evaluated by enzyme-linked immunosorbent assay (ELISA), double diffusion (DD) and counterimmunoelectrophoresis (CIE). Results: Good correlation was found between ELISA results and those of CIE or DD. Both CIE and ELISA were more sensitive than DD. With CIE and ELISA sera were respectively positive 81.8% (9/11) and 75.0% (9/12), whereas 58.3% (7/12) were positive for DD test. Sera from 2 rabbits with experimental fascioliosis had positive reaction with PmAS antigen by both ELISA and CIE tests. No cross-reactivity was observed using sera from cats with dipylidiasis or from healthy cats. Conclusions: Results showed that both ELISA and CIE were equally sensitive tests for paragonimiosis diagnosis but could not be used for differential diagnosis of P. mexicanus and F. hepatica infections due to cross-reaction.